Documentation of neurovascular status in supracondylar fractures and the development of an assessment proforma. Issue 6 (3rd July 2012) - Mayne, Alistair Ivan William; Perry, Daniel C; Stables, Gareth; Dhotare, Satish; Bruce, Colin E
Abstract : Background: Supracondylar fractures are associated with a high incidence of neurovascular complications. Comprehensive clinical evaluation is a necessity when children with these injuries present to the emergency department. Neurovascular assessment can be difficult due to pain, anxiety and the young age of these patients; however, it is crucial findings are well documented to identify patients requiring urgent surgical intervention, in addition to allowing the neurovascular status to be monitored over time. The aim of this study was to evaluate the preoperative neurovascular documentation in children presenting with displaced supracondylar fractures and devise an emergency department assessment proforma to facilitate comprehensive evaluation. Methods: A retrospective case-note review was performed on patients with Gartland grades 2 and 3 supracondylar fractures observed in a 2-year period from July 2008 to July 2010. Results: 137 patients were included; only 12 patients (8.8%) and 19 patients (13.9%), respectively, had a complete preoperative neurological or vascular assessment documented. Regarding the individual nerves, 59 (43.1%) patients had median nerve integrity documented, 55 (40.1%) ulnar nerve and 49 (35.8%) radial nerve integrity documented. Only 18 patients (13.1%) had their anterior interosseous nerve (AIN) function documented. Conclusions: Preoperative documentation of neurovascular status in children with displaced supracondylar fractures was poor. Documentation of AIN examination was particularly poor. The introduction of a proforma (Liverpool upper limb fracture assessment) is proposed to increase documentation of neurovascular assessment and optimise emergency department evaluation of children presenting with upper limb injuries.